Dose-Dependent Pharmacokinetics of Tofacitinib in Rats: Influence of Hepatic and Intestinal First-Pass Metabolism - Ji Sang Lee; So Hee Kim (MDPI AG, 2019)
This study investigated the pharmacokinetics of tofacitinib in rats and the effects of first-pass metabolism on tofacitinib pharmacokinetics. Intravenous administration of 5, 10, 20, and 50 mg/kg tofacitinib showed that the dose-normalized area under the plasma concentration-time curve from time zero to infinity (AUC) was significantly higher at 50 mg/kg than at lower doses, a difference possibly due to saturation of the hepatic metabolism of tofacitinib. Oral administration of 10, 20, 50, and 100 mg/kg tofacitinib showed that the dose-normalized AUC was significantly higher at 100 mg/kg than at lower doses, a difference possibly due to saturation of the intestinal metabolism of tofacitinib. Following oral administration of 10 mg/kg tofacitinib, the unabsorbed fraction from the rat intestine was 3.16% and the bioavailability (F) was 29.1%. The AUC was significantly lower (49.3%) after intraduodenal, compared to intraportal, administration, but did not differ between intragastric and intraduodenal administration, suggesting that approximately 46.1% of orally administered tofacitinib was metabolized through an intestinal first-pass effect. The AUC was also significantly lower (42%) after intraportal, compared to intravenous, administration, suggesting that the hepatic first-pass effect on tofacitinib after entering the portal vein was approximately 21.3% of the oral dose. Taken together, these findings suggest that the low F of tofacitinib is due primarily to intestinal first-pass metabolism.